Accounting for investments. - Subramani, R. Venkata (John Wiley & Sons (Asia), 2009)
The 2008 financial crisis highlighted the need for responsible corporate governance within financial institutions. The key to ensuring that adequate standards are maintained lies with effective accounting and auditing standards. biAccounting for Investments: Equities, Futures and Options/i/b offers a comprehensive overview of these key financial instruments and their treatment in the accounting sector, with special reference to the regulatory requirements. The book uses the US GAAP requirements as the standard model and the IFRS variants of the same are also given. biAccounting for Investments/i/b starts from the basics of each financial product and:ullidefines the productlianalyses the structure of the productlievaluates its advantages and disadvantageslidescribes the different events in the trade cyclelielaborates on the accounting entries related to these events./ul The author also explains how the entries are reflected in the general ledger accounts, thus providing a macro level picture for the reader to understand the impact of such accounting. Lucidly written and informative, biAccounting for Investments/i/b is a comprehensive guide for any professional dealing with these complex products. It also provides an accessible text for technology experts who develop software and support systems for the finance industry.